2018
DOI: 10.1016/j.pecs.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol from corn stover – a review and technical assessment of alternative biotechnologies

Abstract: Reviewing the literature from the last decade regarding the bioconversion of corn stover into ethanol, 474 references were identified containing 561 datasets. We found 144 datasets which were sufficiently consistent and detailed to address the current state of the art of corn stover conversion to bioethanol, and we were able to categorise 93% of these datasets into eight different technological configurations for the production of bioethanol, based on the pretreatment approaches used. After pretreating, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 142 publications
3
60
0
5
Order By: Relevance
“…Unfortunately, with the current rate of fossil fuel consumption, it is expected that reserves will be exhausted within the next 40 to 50 years. More importantly, the burning of fossil fuels contributes to global warming due to greenhouse gas emissions, causing climate change, a rise in sea levels, loss of biodiversity, and urban pollution [1][2][3]. Among the alternative fuels options, bioethanol offers an immediate solution because it does not require to modify the current transport infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, with the current rate of fossil fuel consumption, it is expected that reserves will be exhausted within the next 40 to 50 years. More importantly, the burning of fossil fuels contributes to global warming due to greenhouse gas emissions, causing climate change, a rise in sea levels, loss of biodiversity, and urban pollution [1][2][3]. Among the alternative fuels options, bioethanol offers an immediate solution because it does not require to modify the current transport infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of bioethanol, most of it is produced from edible biomass by fermentation, which causes a competition with food naturally. Although bioethanol was generated from non‐edible biomass, its production is still in its infancy . Glycerol is generated as a by‐product during the manufacture of biodiesel from renewable sources .…”
Section: Introductionmentioning
confidence: 99%
“…Although bioethanol was generated from non-edible biomass, its production is still in its infancy. [12] Glycerol is generated as a by-product during the manufacture of biodiesel from renewable sources. [13] In most cases, more than stoichiometric base were required during the hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Corn stover is a desirable raw material for producing cellulosic ethanol [5][6][7]. Corn stover for ethanol production can provide co-benefits because it can improve energy security and reduce air pollution [8][9][10][11][12][13]. Corn stover for fuel production has a great potential in China because corn made up 39.2% of all cereals in 2017 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Because of different system boundaries and functional unit (FU), the results related to life-cycle GHG emission reductions, at least in their numerical forms, cannot always be compared directly with most of the reported cases. Based on some literature reviews [8][9][10]13,[26][27][28], using corn stover for ethanol production is urgent and necessary considering energy and environment profits. However, there are no studies found in the available literature to assess the potential reductions in GHG and PM 2.5 emissions from corn stover based ethanol while considering corn stover geographical distributions.In this study, the available corn stover for ethanol production and its emission reduction factors per unit corn stover were combined to assess the environmental impacts.…”
mentioning
confidence: 99%